FACTORS ASSOCIATED WITH BREAKFAST CONSUMPTION BEHAVIOR AMONG HIGH SCHOOL STUDENTS AT SRISONGKHRAM WITTAYA SCHOOL, LOEI PROVINCE - พลเยี่ยม สุพรรัตน์; ล่ำสัน พรพิมล; ไชยตอกเกี้ย สุระเดช (Primary Health Care Journal (Northeastern Edition), 2025)
Breakfast is considered the most important meal of the day, as the body requires nutrients and energy to support its organs and brain function. Skipping breakfast can lead to insufficient nutrient and energy intake, resulting in fatigue, reduced physical activity, and lack of concentration in class. This cross-sectional analytical study aimed to examine factors associated with breakfast consumption behavior among high school students at Srisongkhram Wittaya School in Loei Province. The sample consisted of 181 students, selected through simple random sampling. Data were collected using a questionnaire with an Index of Item-Objective Congruence (IOC) between 0.67 and 1.00 and a reliability coefficient of 0.85. Descriptive statistics, including percentages, means, and standard deviations, were used for data analysis, along with inferential statistics such as point-biserial, eta, and Pearson’s correlation coefficients. The findings revealed that the majority of students had a moderate level of knowledge regarding breakfast consumption (57.5%, Mean = 9.02, SD = 2.89), a moderate level of attitude (69.6%, Mean = 2.57, SD = 0.48), and a moderate level of breakfast consumption behavior (97.2%, Mean = 2.88, SD = 0.31). Factors significantly associated with breakfast consumption behavior included parental income (r = 0.166, p = .025), parental occupation (r = 0.280, p = .026), age-appropriate weight (r = 0.424, p = .024), and knowledge of breakfast consumption (r = -0.304, p < .001). In conclusion, parental income, parental occupation, and age-appropriate weight showed a positive relationship with breakfast consumption behavior, while knowledge about breakfast consumption showed a negative correlation. It is recommended that nutrition education be promoted alongside positive attitude formation and support for school breakfast programs to enhance students’ overall health and well-being.